Knowledge and attitudes towards special educational needs: A study with future teachers - Chura-Quispe, Gilber; Vargas-Fuentes, Julisa Alexandra; Padilla Díaz, Omar Eduardo; Laura De La Cruz, Bianca Daisa; Valdez Copaja, Rossana; Nue Caballero, Patricia Rosa (LPMPP Universitas Negeri Yogyakarta, 2025)
The training of teachers is continually adapting to the needs demanded by today’s society. Special educational needs (SEN) currently represent a challenge that future teachers must approach with favourable attitudes and a willingness to engage. The aim of this study is to assess the impact of knowledge in inclusive education on attitudes towards special educational needs among university students. The research employs a cross-sectional and explanatory design, involving 406 university students from teacher training programmes in Peru. Data were collected using the Inclusive Education Questionnaire and the Attitude Scale towards the Inclusion of Students with SEN, both of which demonstrated adequate validity and reliability indices. The results confirm that teachers' attitudes towards special educational needs are positively and significantly affected by knowledge of the definition and characteristics of inclusive education (β = 0.438, p < 0.05), the importance of this knowledge (β = 0.139, p < 0.05), and knowledge of children's disabilities (β = 0.388, p < 0.05). In conclusion, attitudes can be explained through the knowledge acquired by university students during their professional training. Therefore, teacher education in pedagogy is essential for improving the quality of inclusive education in basic education schools.